Perfilhamento e anatomia foliar do capim-mombaça adubado com nitrogênio e irrigado sob pastejo - Piotto, Vanessa Cristina (2012)
The experiment was carried out in Santo Inácio´s city in the northwest region of Paraná, aiming to assess the tiller density, number and weight of leaf and stem, tiller, tiller dynamics (rate of appearance and death tiller), and foliar area components of leaf tissue (leaf anatomy) of Mombaça grass (Panicum maximum Jacq. cv. Mombaça) fertilized with nitrogen levels in seasons, irrigated and grazing with rotational stocking. The total pasture area was approximately two hectares, divided into four blocks. Each block was subdivided into four paddocks (experimental units), with a total of 16 paddocks, with 1600 m². The experimental design was randomized blocks with split plots and four replications, and the plots, were evaluated in the four seasons: spring, summer, autumn and winter. The treatments (plots) were: Mombaça grass + 0 kg nitrogen (N) ha-1 year (control), Mombaça grass + 200 kg N ha-1year, Mombaça grass + 400 kg N ha-1year and Mombaça grass + 800 kg N ha-1year. The experimental area was irrigated using the sprinkler system. For estimation of tillers population were estimated, they are recorded within an area of 0.70 x 1.50 m2, each pre-grazing. To assess the number of leaves and weight of the tiller,30 tillers were collected at random and representing the area, and separated into leaf and stem + sheath. To study the demographics of tillers were marked five clumps per paddock, all of which were representative of the experimental unit so the clumps. After six or seven days the animals were removed from experimental units, these clumps were re-evaluated, where new tillers were marked and the dead, were recorded. To assess the leaf area, were collected ten slides of each experimental unit before grazing. Another five leaf blades were collected from each experimental unit, and then were cut into pieces about 1 cm and packaged in glass and covered with a FAA 50 (formaldehyde+ acetic aced+ ethanol). The tiller density varied with increasing doses of nitrogen applied, and in the seasons, higher values were observed for the summer, followed by spring, autumn and winter. The number of live leaves obtained negative effect for increasing nitrogen levels in summer season, and in the fall, the effect was reversed. The mass of leaf and stem obtained interaction effect between nitrogen rates applied and the seasons in which the greatest mass of leaves and lower stem mass was found at the dose of 800 kg N ha-1yr. The tiller density increased linearly with increasing doses of nitrogen applied to the stations, we observed higher values for the summer season, and followed the seasons of spring, autumn and winter. The number of leaves remained roughly constant-between doses of nitrogen applied, obtaining greater variation only in the fall season. The weight of leaf effects achieved at doses applied in the seasons of autumn and winter and the weight of stem in the summer season, being higher for the dose of 0 kg N ha-1 and to lower the dose of 800 kg N ha- 1year. The rate of tillers was relatively larger dose of 0 kg N ha-1 and greater variation among nitrogen levels occurred in the summer season. To the rate of tillers mortality lowest values were found for the at dose of 800 0 kg N ha-1 and in stations, the highest rate occurred during the winter season. For leaf area was interaction between nitrogen and the seasons in which the highest values were found for a dose of 800 kg N ha-1, and the stations were no significant effects for the fall and winter. For leaf anatomy, there there was no significant effect of nitrogen applied and seasons for adaxial and abaxial epidermis, sclerenchyma, bundle sheath, and vascular bundle. For the mesophyll linaer positive effect was observed for increasing levels of nitrogen applied.